Private Landowners’ Willingness to Enroll Their Properties in a Public Hunting Access Program in Northeast Missouri - Thomas B. Treiman; Thomas V. Dailey; Ronald A. Reitz; Heather J. Scroggins (National Quail Symposium Proceedings, 2017)
State wildlife agencies have successfully used public hunting access fees to increase hunting opportunity and to provide a financial incentive to private landowners for maintaining habitat. Typical payments per hectare (ac) include $3.29 ($1.25) on average in Kansas, $2.47-$3.71($1-$1.50) for pheasant hunting in Colorado, $2.47-$12.36 ($1–$5) in North Dakota for pheasant hunting, and $4.45 ($1.80) on average in South Dakota. We studied the USDA Conservation Reserve Program (CRP) in 2004 in Adair, Knox, Macon, Monroe, Ralls, Randolph, Schuyler, and Scotland counties in northeast Missouri as part of a quail and songbird habitat restoration initiative. CRP is prominent in these counties with 83,040 ha (205,197 ac) enrolled. We conducted a mail-back survey of all CRP contract holders, totaling 3,283 landowners to study their willingness to enroll their properties in a hypothetical public- access hunting program. The survey was designed to provide information about landowner demographics, attitudes toward wildlife and hunting, and knowledge of wildlife habitat management aspects of the CRP. We used the Kansas Department of Wildlife and Parks Walk-In Hunting Access Program as an example for questions related to the concept of public-access hunting, and presented landowners with hypothetical annual lease payments for enrolling, using a discrete-choice modeling framework. Survey response rate was relatively high at 59.5%. The average respondent had 34.6 ha (85.5 ac) enrolled in CRP, and field size averaged 6.47 ha (16.0 ac), ranging from 0.04 to 84.9 ha (0.1–209.7 ac). Wildlife as a product of the CRP was ‘very’ or ‘somewhat important’ to 89% of respondents and, among a list of wildlife species and native plants, northern bobwhite (Colinus virginianus) was most popular with 80% of respondents checking ‘very’ or ‘somewhat important’ on the survey. The corresponding values were 53–66% for wild turkey (Meleagris gallopavo), deer, rabbit, pheasant, and songbirds. We asked if landowners would enroll any of their CRP land in a public-access hunting program (PAHP). We used 8 different versions of the survey, each with a different ‘offer’ level in the question to evaluate the potential costs of a PAHP program. The structure of the survey specified whether landowners would accept payment of $X/ac, where X was one value randomly selected from the set of $1, $2, $3, $4, $5, $7, $10, or $20. None of respondents chose ‘yes’ at a PAHP value of $0, 91.9% chose ‘no’, and 8.1% chose ‘don’t know’; respective values ($) and choices (%) (yes, no, don’t know) were: $1-1.7%, 91.3%, and 6.9%; $2-3.0%, 90.2%, and 6.8%; $3-4.0%, 84.9%, and 11.2%; $4-3.4%, 87.7%, and 9.0%; $5- 4.7%, 83.4%, and 11.9%; $7-7.1%, 82.1%, and 10.7%; $10-8.4%, 77.0%, and 14.7%; and $20-14.8%, 71.3%, and 13.9%. Respondents were asked what kind of hunting they would allow on their land in a PAHP program. Almost all would allow deer hunting, whereas only 48% would allow small game hunting, such as quail. Respondents were given a choice of reasons for not enrolling in PAHP and, of the negative responses, . 90% said that having ‘strangers on my land’ was an issue while . 85% cited ‘damage to property, crops or livestock’ as a potential problem; . 90% mentioned the need for a liability law protecting landowners. We asked those landowners responding ‘yes’ to PAHP how many of their CRP acres they would enroll. At a payment level of $2/ac ($4.94/ha), ~ 3% of landowners said they would enroll an average of about 86% of their CRP acres. Two dollars per acre is well within the range of payments offered by neighboring states. This would amount to . 2,023 ha (5,000 ac) (of the 83,040 ha total CRP) area being enrolled in the 8 Missouri counties in this study, at an annual cost of about $10,500. About 1,012 ha (2,500 ac) would be designated for quail hunting of this hypothetical PAHP area, based on respondents’ answers to what type of hunting they would allow. We estimate that 5,261 ha (13,000 ac) would be enrolled with 2,489 ha (6,150 ac) open for quail hunting at an annual cost of about $90,000 if the payment level was raised to $7/ac ($17.30/ha). There is potential to improve the feasibility of CRP lands for bobwhite hunting in northeast Missouri by adding a public-access hunting incentive, but managers will be challenged to use this approach successfully. Landowners’ inclination to allow access for deer hunting, but not for quail hunting, reduces an agency’s justification for using quail hunting access as an approach to improve conservation of bobwhites, in addition to the relatively high cost.
Keywords: Colinus virginianus; economics; financial incentives; Kansas Walk In Program; landowner attitudes; Missouri; motivation; private lands; public access hunting; values; willingness-to-accept payment (WTA)